1996
DOI: 10.1055/s-2007-1015709
|View full text |Cite
|
Sign up to set email alerts
|

Gadodiamid und Gadolinium-DTPA als intravenöse Kontrastmittel in der Computertomographie

Abstract: Sufficient parenchymal enhancement in CT studies cannot be achieved with the available gadolinium-based contrast mediums. They might be helpful if only short time vascular enhancement is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Both arterial and venous cervical or thoracic vessels could be enhanced to 100 Hounsfield units with a bolus injection, and sufficient enhancement for diagnosis of dissections/aneurysms of arterial vessels could be achieved. Attenuation of the parenchymal organs were insufficient in all these investigations [8][9][10][11][12][13][14]; therefore, gadoliniumcontaining CM are not useful for CT examinations of these organs.…”
Section: Gadolinium-chelates and Ct In Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Both arterial and venous cervical or thoracic vessels could be enhanced to 100 Hounsfield units with a bolus injection, and sufficient enhancement for diagnosis of dissections/aneurysms of arterial vessels could be achieved. Attenuation of the parenchymal organs were insufficient in all these investigations [8][9][10][11][12][13][14]; therefore, gadoliniumcontaining CM are not useful for CT examinations of these organs.…”
Section: Gadolinium-chelates and Ct In Clinical Practicementioning
confidence: 99%
“…Studies reporting experiences with gadopentetate (Magnevist) for CT examinations ml/s); cave: very short vessels up to 100 HE; parenchyma of liver duration of the bulos with short and kidney was not sufficiently enhanced time window for optimal contrasting[10] 5 0.2 mmol/kg b.w. No side effects Parenchymal enhancement did not exceed 25%, arterial enhancement peak was 75%.…”
mentioning
confidence: 99%
“…That is why an adequate parenchymal enhancement cannot be achieved today in CT studies with i.v. administration of Gd-DTPA (5). A 1-mmoV1 solution is currently being tested for market approval and might solve this problem (6).…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, it has been suggested that gadoliniumbased contrast media could be used in place of iodinated agents for radiological examinations in patients with significant renal impairment [1][2][3][4][5]. The Contrast Media Safety Committee of the European Society of Urogenital Radiology recently concluded upon an extensive review of the literature that the use of gadolinium-based contrast media for radiographic examinations to avoid nephrotoxicity in patients with renal impairment is not recommended since they are more nephrotoxic than iodinated contrast media in equivalent X-ray attenuating doses [6].…”
Section: Introductionmentioning
confidence: 99%